Influencia del cuidador en el declive cognitivo y funcional de personas con demencia: revisión sistemática. (2021)
Dementia is a neurodegenerative disease that requires the accompaniment of a caregiver who is in charge of assisting and supervising basic and psychosocial needs. The objective of this article was to determine the influence of the caregiver on the cognitive and functional decline of patients with dementia. The method was a systematic review by searching the Scopus, Pubmed and Science Direct databases between the years 2010-2020. In conclusion, the informal caregiver condition was the most reported by the investigations, generally assumed by wives and children; Caregiver characteristics such as personality, subjective interpretations of the functional status of adults with dementia, and caregivers' coping strategies were associated with a decrease in the rate of cognitive and functional impairment of people with dementia.